Restraining the Political through Stay-Away Orders: The Case of Occupy Oakland - Brissette, Emily (Social justice, 2020)
The article discusses how political leaders and governments restrain social movements by examining the case of Occupy Oakland in California in 2012. Also cited are the move by Oakland city officials and the Alameda County District Attorney (DA) to use stay-away orders to prevent the arrested protesters from joining the protests, and the efforts by Occupy Oakland and the American Civil Liberties Union (ACLU) to contest the orders.